Assessing the role of color cues and people's beliefs about color-flavor associations on the discrimination of the flavor of sugar-coated chocolates. - Levitan, C; Zampini, M; Li, R; Spence, C (2008)
We report 2 experiments designed to investigate the effect of people's prior beliefs concerning specific color-flavor associations on their ability to discriminate the flavor of colored sugar-coated chocolate sweets. The participants in our study judged whether pairs of Smarties had the same flavor or not. In our first experiment, the participants either performed the task with their eyes open or else while wearing a blindfold to eliminate any visual cues. We used pairs of Smarties that either did or did not differ in flavor. In making a sighted comparison between red and green Smarties, the participants were more likely to judge them as tasting the same if they believed all non-orange Smarties to be identical in flavor and as different in flavor if they did not hold such a belief. The ability of our participants to discriminate orange Smarties from the red and green Smarties was unaffected by their prior belief that orange Smarties taste different. In a second experiment, participants' ratings of their certainty of there being a difference in flavor between a red and an orange Smartie that either tasted the same or different were affected by their prior beliefs-those participants who expected a difference were more likely to report a difference than those without any such prior expectation. Taken together, these results demonstrate that people's expectations concerning color-flavor associations can modulate their flavor discrimination responses, even for a familiar food product such as Smarties.